Implementasi Peraturan Pemerintah Nomor 40 Tahun 2017 Di Kabupaten Karimun - Hafzana Bedasari; Siti Maharani (UIR Press, 2020)
Free Trade Zone and Free Port (KPBPB) is one of the National Strategic Areas in Riau Islands Province. The Affirmation of Karimun Regency to become KPBPB is elaborated in Government Regulation Number 40 of 2017 concerning Amendment to Government Regulation Number 48 of 2007 concerning KPBPB. The implementation of the KPBPB in Karimun Regency has been going on for almost 12 years, but the implementation encountered a variety of obstacles so that the implementation of the KPBPB has not been able to run effectively. The purpose of this research is to determine the implementation and the factors that influence the implementation of government regulation number 40 of 2017 concerning KPBPB in Karimun Regency, this research was carried out at BP Karimun's office. The type of research used was descriptive qualitative, and analyzed data using Interactive Model analysis techniques from miles huberman. Based on the results of the study it can be concluded that the analysis of the preparation of the implementation of Government Regulation number 40 of 2017 concerning changes to government regulation number 48 of 2007 concerning the KPBPB in Karimun Regency has been going well, judging by the factors of communication, resources, disposition, and bureaucratic structure. In addition its strategic location, however it is felt there are still a few deficiencies here and there including the still fat organizational structure of BP Karimun.